Technologies of synthesis of organic substances by microorganisms using waste biodiesel production - Pirog, Tatiana; Gritsenko (Manzhula), Natalia; Sofіlkanich (Morozova), Anna; Savenko, Inga (My University, 2015)
We describe here literature and our experimental data concerning microbial synthesis using waste biodiesel production, mono- and dihydric alcohols (1,3-propanediol, 2,3-butanediol, butanol, ethanol), polyols (mannitol, erythritol, arabitol), organic acids (citric, succinic, lactic, glyceric), polymers and compounds with a complex structure (polysaccharides, polyhydroxyalkanoates, surfactants, cephalosporin, cyanocobalamin). In some mentioned cases recombinant producer strains were used. It was shown that due to the presence of potential inhibitors in the composition of technical (crude) glycerol (methanol, sodium and potassium salts), the efficiency of synthesis of most microbial products on such a substrate is lower than on the purified glycerol. However, the need of utilization of this toxic waste (storage and processing of crude glycerol is a serious environmental problem due to the high alkalinity and the content of methanol in it), compensates the lower rates of synthesis of the final product. Furthermore, currently considering the volumes of crude glycerol formed during the production of biodiesel, microbial technologies are preferred for its utilization, allowing realizing biosynthesis of practically valuable metabolites in the environment with the highest possible concentration of this waste. Using of crude glycerol as a substrate will reduce the cost of products of microbial synthesis and increase the profitability of biodiesel production.
Keywords: кафедра біотехнології і мікробіології; biodiesel; technical (crude) glycerol; products of microbial synthesis; біодизель; технічний гліцерол; продукти синтезу органічних сполук мікроорганізмами; биодизель; технический глицерол; продукты синтеза органических соединений микроорганизмами